Respuesta :
1. 4(1 - 3x) + 7x = 9
Distribute
4 - 12x + 7x = 9
Isolate x terms
-12x + 7x = 9 - 4
Combine like terms
-5x = 5
Divide
x = -1
2. 9 - 5x = 12 - (6x + 7)
Distribute
9 - 5x = 12 - 6x - 7
Move terms to get x terms on one side
-5x + 6x = -9 + 12 - 7
Combine like terms
x = -4
Distribute
4 - 12x + 7x = 9
Isolate x terms
-12x + 7x = 9 - 4
Combine like terms
-5x = 5
Divide
x = -1
2. 9 - 5x = 12 - (6x + 7)
Distribute
9 - 5x = 12 - 6x - 7
Move terms to get x terms on one side
-5x + 6x = -9 + 12 - 7
Combine like terms
x = -4
Answer:
1.) x = -1
2.) x = -4
Step-by-step explanation:
1.) 4(1 - 3x) + 7x = 9
=> Use distributive property:
4 - 12x + 7x = 9
=> Combine like terms:
4 - 5x = 9
=> Isolate 5x:
-5x = 5
=> Isolate x:
x = 5/-5
=> Simplify:
x = -1
2.) 9 - 5x = 12 - (6x + 7)
=> Use distributive property:
9 - 5x = 12 -6x - 7
=> Combine like terms:
9 - 5x = 5 - 6x
=> Isolate x to one side:
9 + x = 5
x = -4
Hope this helps!